PEMBERDAYAAN EKONOMI MASYARAKAT DI KAMPUNG BATIK CIBULUH KELURAHAN CIBULUH KOTA BOGOR JAWA BARAT OLEH LPEM BAZNAS - Fajar Abdurrachman; WG Pramita Ratnasari (Jurnal Kommunity Online, 2023)
Indonesia has many different cultures produced by various ethnic groups of people in every region in Indonesia, one of which is Batik. Batik is a unique Indonesian art that has been worldwide and even UNESCO has designated Batik as Indonesian cultural heritage. LPEM BAZNAS utilizes Batik culture to empower people in the Bogor area, precisely in Cibuluh Batik Village. The empowerment carried out is batik training through the mustahik entrepreneur program conducted by BAZNAS. This study aims to determine the process of economic empowerment carried out by LPEM BAZNAS, and to find out the results obtained by craftsmen while joining the cottage industry.This research was conducted using descriptive qualitative research with data collection techniques used, namely observation, interviews, and documentation studies. This study uses the theory of stages of empowerment by Sulistiyani, and the theory of success of empowerment to see the results proposed by Schuler, Heshemi and Riley quoted in Edi Suharto's book.The results of this study indicate that the utilization of local cultural potential, namely Batik Bogor by BAZNAS, has succeeded in improving the economy of the people of Kampung Batik Cibuluh.